Factors related to the prevention of early marriage in adolescents RP SNC Fannaz Sunggal Deli Serdang: A cross-sectional study - Ida Lestari Tampubolon; Yetti Dynaria Siregar; Dwiana Kartika Putri; Nayodi Permayasa (Institute of Computer Science (IOCS), 2026)
Early marriage is a public health problem that has an impact on reproductive health, education, psychology, and adolescent welfare. Early marriage prevention needs to be supported by knowledge, attitudes, the role of parents, and access to good reproductive health information. This study aims to determine factors related to the prevention of early marriage in adolescents at RP SNC FANNAZ Sunggal Deli Serdang. This study uses a quantitative design with a cross-sectional approach. The research sample was 85 adolescents. Data were collected using questionnaires and analyzed univariate and bivariate using chi-square tests. The results showed that there was a relationship between adolescents' knowledge of early marriage and prevention of early marriage with a value of p=0.002, adolescents' attitudes with a value of p=0.004, the role of parents/families with a value of p=0.006, and access to reproductive health information with a value of p=0.001. Therefore, reproductive health education and family involvement need to be improved to prevent early marriage.